Music and Creativity in Healthcare Settings : does music matter? - Moss, Hilary, Dr (Routledge, 2022)
Through a series of vivid case studies, Music and Creativity in Healthcare Settings: Does Music Matter? documents the ways in which music brings humanity to sterile healthcare spaces, and its significance for people dealing with major illness. It also considers the notion of the arts as a vessel to explore humanitarian questions surrounding serious illness, namely what it is to be human. Overarching themes include: taking control; security and safety; listening; the normalization of the environment; being an individual; expressing emotion; transcendence and hope and expressing the inexpressible. With an emphasis on service user narratives, chapters are enriched with examples of good practice using music in healthcare. Furthermore, a focus on aesthetic deprivation contributes to debates on the intrinsic and instrumental value of music and the arts in modern society. This concise study will be a valuable source of inspiration for care givers and service users in the health sector; it will also appeal to scholars and researchers in the areas of Music medicine and music Therapy, and the Medical Humanities.